2018
DOI: 10.18257/raccefyn.560
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the structural ordering of the Sr2SbMnO6 perovskite as a function of temperature

Abstract: El material cerámico policristalino Sr2SbMnO6 se sintetizó mediante el método convencional de reacción en estado sólido. La ruta de síntesis usada difirió de otras reportadas en la literatura en que se usó SrO en lugar de SrCO3 como precursor del Sr. Los patrones de difracción de rayos X obtenidos a temperaturas entre 25 y 1.400 °C se estudiaron mediante el método de refinamiento de Rietveld con el programa Generalized Structure Analysis System (GSAS). Los resultados revelaron que la estructura era tetragonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(8 reference statements)
1
1
0
Order By: Relevance
“…On the other hand, to our knowledge the only values reported for the parameters of the tetragonal P/4mnc phase are those experimentally obtained by (Parada et al, 2018) which are comparable to ours, as shown in the table 2. In adittion, it is noticed the negative value for the cohesive energy, which proves the stable character of this phase and consequently new evidence of its existence.…”
Section: Structural Parameterssupporting
confidence: 88%
See 1 more Smart Citation
“…On the other hand, to our knowledge the only values reported for the parameters of the tetragonal P/4mnc phase are those experimentally obtained by (Parada et al, 2018) which are comparable to ours, as shown in the table 2. In adittion, it is noticed the negative value for the cohesive energy, which proves the stable character of this phase and consequently new evidence of its existence.…”
Section: Structural Parameterssupporting
confidence: 88%
“…Editor: Rafael González Hernández *Corresponding autor: William Sosa Correa; woscydm@gmail.com transition metal, respectively. The Sr 2 MnSbO 6 perovskite is one compound of this type, and it has been synthetized via molten salt synthesis (MSS) method and convectional solid-state methods for example by (Cheah et al, 2006;Ivanov et al, 2009;Parada et al, 2018;Preethi-Meher et al, 2012). Experimental studies of Sr 2 MnSbO 6 have shown that this compound presents ferroelectric and ferromagnetic behavior in the I4m, I4mm, I4mcm phases, as well as it exhibits high dielectric constant in the cubic phase Fm-3m (Antara, et al, 2011;Foster, et al,1997;Majhi & Varma, 2007).…”
Section: Physical Sciencesmentioning
confidence: 99%